2011
DOI: 10.1056/nejmoa1101245
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Vaccine against Experimental Human Norwalk Virus Illness

Abstract: Background Noroviruses cause epidemic and sporadic acute gastroenteritis. No vaccine is available to prevent norovirus illness or infection. Methods We conducted a randomized, double-blind, placebo-controlled, multicenter trial to assess the safety, immunogenicity, and efficacy of an investigational, intranasally delivered norovirus viruslike particle (VLP) vaccine (with chitosan and monophosphoryl lipid A as adjuvants) to prevent acute viral gastroenteritis after challenge with a homologous viral strain, No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
418
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(432 citation statements)
references
References 37 publications
8
418
2
4
Order By: Relevance
“…7 The VP1 protein can self-assemble into viruslike particles (VLPs) that are structurally similar to native virions. Clinical trials testing the efficacy of HuNoV VLPs as vaccine candidates administered intranasally or intramuscularly have demonstrated modest short-term (up to 1 month) protection from developing severe disease, 8,9 results that are encouraging but do not address the critical questions of immunity duration or cross-reactive protective immunity. Development of potentially more effective live attenuated viral vaccines has long been hindered by an inability to culture HuNoVs.…”
Section: Introductionmentioning
confidence: 99%
“…7 The VP1 protein can self-assemble into viruslike particles (VLPs) that are structurally similar to native virions. Clinical trials testing the efficacy of HuNoV VLPs as vaccine candidates administered intranasally or intramuscularly have demonstrated modest short-term (up to 1 month) protection from developing severe disease, 8,9 results that are encouraging but do not address the critical questions of immunity duration or cross-reactive protective immunity. Development of potentially more effective live attenuated viral vaccines has long been hindered by an inability to culture HuNoVs.…”
Section: Introductionmentioning
confidence: 99%
“…125 Two doses of vaccine or placebo were administered intranasally to healthy 18-50 y adults followed by homologous inoculation with HuNoV. The participants enrolled in this study were likely to develop NoV -associated gastroenteritis due to the expression of O or A blood groups and a functional FUT2 gene.…”
Section: Human Trialsmentioning
confidence: 99%
“…This study confirmed HuNoV infection however at a lower rate than those previously reported in other human challenge studies. 125,127 The most recent published data are the results of the phase I clinical trial using VLPs containing GI.1 and GII.4 administered intramuscularly to 18-49 y healthy adults. 130 The results show the ability of this bivalent vaccine to induce serum antibody responses to GI.1 and GII.4 antigens albeit higher in the former.…”
Section: Human Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A monovalent GI.1VLP vaccine administered via the intranasal (IN) route was shown to provide good protection in a clinical trial. 7 To overcome the epidemiological differences of GI.1 and GII.4 genotypes, a bivalent VLP vaccine carrying GI.1 and GII.4 genotypes was proposed for IN administration and shown to be immunogenic without the use of adjuvant in a guinea pig model. 8 However, intramuscular administration of monovalent GI.1VLPs has been shown to achieve better antigen delivery and antibody responses in adults at a lower dosage than IN immunization.…”
Section: Introductionmentioning
confidence: 99%